A calcium-accumulating region, CAR, in the channel Orai1 enhances Ca(2+) permeation and SOCE-induced gene transcription - Frischauf, Irene; Zayats, Vasilina; Deix, Michael; Hochreiter, Anna; Jardin, Isaac; Muik, Martin; Lackner, Barbara; Svobodová, Barbora; Pammer, Teresa; Litviňuková, Monika; Sridhar, Amrutha Arumbakam; Derler, Isabella; et al. (Science signaling, 2015)
The Ca(2+) release-activated Ca(2+) channel mediates Ca(2+) influx in a plethora of cell types, thereby controlling diverse cellular functions. The channel complex is composed of stromal interaction molecule 1 (STIM1), an endoplasmic reticulum Ca(2+)-sensing protein, and Orai1, a plasma membrane Ca(2+) channel. Channels composed of STIM1 and Orai1 mediate Ca(2+) influx even at low extracellular Ca(2+) concentrations. We investigated whether the activity of Orai1 adapted to different environmental Ca(2+) concentrations. We used homology modeling and molecular dynamics simulations to predict the presence of an extracellular Ca(2+)-accumulating region (CAR) at the pore entrance of Orai1. Furthermore, simulations of Orai1 proteins with mutations in CAR, along with live-cell experiments, or simulations and electrophysiological recordings of the channel with transient, electrostatic loop3 interacting with loop1 (the site of CAR) determined that CAR enhanced Ca(2+) permeation most efficiently at low external Ca(2+) concentrations. Consistent with these results, cells expressing Orai1 CAR mutants exhibited impaired gene expression stimulated by the Ca(2+)-activated transcription factor nuclear factor of activated T cells (NFAT). We propose that the Orai1 channel architecture with a close proximity of CAR to the selectivity filter, which enables Ca(2+)-selective ion permeation, enhances the local extracellular Ca(2+) concentration to maintain Ca(2+)-dependent gene regulation even in environments with relatively low Ca(2+)concentrations.
Keywords: genetická transkripce; Calcium; Membrane Proteins; Drosophila melanogaster; Humans; Protein Structure, Secondary; Stromal Interaction Molecule 1; ORAI1 Protein; Transcription, Genetic; Drosophila Proteins; vápník; permeabilita buněčné membrány; Ion Transport; lidé; HEK293 Cells; sekundární struktura proteinů; zvířata; protein STIM1; proteiny Drosophily; Cell Membrane Permeability; HEK293 buňky; iontový transport; membránové proteiny; Animals; protein ORAI1